1998
DOI: 10.1086/311434
|View full text |Cite
|
Sign up to set email alerts
|

UVCS/[ITAL]SOHO[/ITAL] Empirical Determinations of Anisotropic Velocity Distributions in the Solar Corona

Abstract: We present a self-consistent empirical model for several plasma parameters of a polar coronal hole near solar minimum, derived from observations with the Solar and Heliospheric Observatory Ultraviolet Coronagraph Spectrometer. The model describes the radial distribution of density for electrons, H , and O and the outflow of O are also significantly larger than the corresponding velocities of H . We discuss the constraints and 5ϩ 0 implications on various theoretical models of coronal heating and acceleration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
228
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(251 citation statements)
references
References 31 publications
23
228
0
Order By: Relevance
“…The model predicts CH plasma to reach 764 km s -1 at 1 AU (with the sonic point at 2.3 ⊙ ), while the dense structure plasma reaches at 1 AU a lower speed of 590 km s -1 (with sonic point at 3.4 ⊙ and a speed lower than the CH plasma speed throughout the corona). This model yields higher proton than electron temperatures in the inner corona, a possibility that has been ignored by previous authors, but it is consistent with spectroscopic measurements that suggest is lower than proton temperatures (e.g., Kohl et al, 1996Kohl et al, , 1998 in CH plasmas. However, Habbal et al (1995) results cannot be blindly applied to plumes, because the dense structures imaged by the coronagraphs have not been unambiguously associated with plumes, but, possibly, with CH boundaries.…”
Section: Empirical Modelssupporting
confidence: 88%
“…The model predicts CH plasma to reach 764 km s -1 at 1 AU (with the sonic point at 2.3 ⊙ ), while the dense structure plasma reaches at 1 AU a lower speed of 590 km s -1 (with sonic point at 3.4 ⊙ and a speed lower than the CH plasma speed throughout the corona). This model yields higher proton than electron temperatures in the inner corona, a possibility that has been ignored by previous authors, but it is consistent with spectroscopic measurements that suggest is lower than proton temperatures (e.g., Kohl et al, 1996Kohl et al, , 1998 in CH plasmas. However, Habbal et al (1995) results cannot be blindly applied to plumes, because the dense structures imaged by the coronagraphs have not been unambiguously associated with plumes, but, possibly, with CH boundaries.…”
Section: Empirical Modelssupporting
confidence: 88%
“…The models were able to produce reasonable parameters for the corona and wind, in compliance with basic observations of the effective wave amplitude as derived from the line width of extreme ultraviolet radiation lines ) that are emitted by heavy ions in the solar transition region. Tu & Marsch (2001) have further used the high-frequency wave-energysweeping mechanism of the previous models to explain also why the O +5 line widths indicate strong perpendicular ion heating (Kohl et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Because the resonant damping rate of the waves is very high, the ions with a low resonance frequency may absorb most of the energy in a short time, and then little is left for protons. However, SOHO observations (Kohl et al 1998) showed that both O 5+ ions and protons are heated, and that heating is indeed needed to explain the widths of EUV emission lines (Wilhem et al 1998). To avoid the problem mentioned above, and suggested a two-step process yielding sizable heating of both O +5 and protons.…”
Section: Introductionmentioning
confidence: 99%
“…In situ measurements of the fast solar wind and remote sensing observations of the solar corona have revealed that the heavy minor ions are faster and hotter than the protons, and they generally are preferentially heated in the perpendicular direction (Feldman et al 1974;Marsch et al 1982;Kohl et al 1998;Li et al 1998;von Steiger & Zurbuchen 2006;Marsch 2006). Although the physical mechanisms responsible for the observed ion behavior are still in debate, it is commonly believed that the dissipation of Alfvén waves may be relevant to the observed ion heating.…”
Section: Conclusion and Discussionmentioning
confidence: 99%